A novel image encryption algorithm combined complex order chaotic system and modified AES - Sun, Jing-yu; Cai, Hong; Zhang, Hao (Multimedia tools and applications, 2024)
Aiming at the security of digital images, this paper proposes an image encryption algorithm based on a chaotic system of complex order and modified Advanced Encryption Standard (AES). A new complex order chaotic system is first proposed. The proposed encryption algorithm utilizes the chaotic system to generate dynamic s-boxes and keys associated with the plaintext, and dynamically introduces index values in each step of the AES, which increases the unpredictability and reduces the number of encryption rounds, leading to better encryption efficiency. Each round of encryption uses a different s-box for SubBytes operations. Each round of encryption is rotated, so the algorithm is suitable for the encryption of irregular images. Combining the advantages of complex-order chaos and improved AES, it has been proven that the proposed scheme has good properties through statistical analysis, differential analysis, correlation comparison, and other related experiments.